2002
DOI: 10.18388/abp.2002_3841
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cyclosporin A on immunological response in lungs of guinea pigs infected with Trichinella spiralis.

Abstract: The effects of cyclosporin A (CsA), a potent immunosuppressive drug with antiparasitic activity, on the innate immunological response in guinea pig lungs during an early period (6th and 14th days) after T. spiralis infection were studied. CsA treatment of T. spiralis-infected guinea pigs caused a significant attenuation of immunological response in lungs by decreasing lymphocyte infiltration into pulmonary alveolar space, inhibiting alveolar macrophage superoxide anion production and lowering both the producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…In mice showing Th1 or Th2 response, two different types of macrophage activation have been described, M-1 (classical) involving induction of iNOS and nitric oxide production and M-2 (alternative) involving arginase induction (Mosser, 2003). We have shown that T. spiralis infection of guinea pigs does not induce nitric oxide production in lung macrophages (Dzik et al, 2002a;2002b) exposed to larval antigens when newborn larvae pass to the muscles. Instead, arginase activity is enhanced in these cells (Dzik et al, 2004), concomitantly with respiratory burst induction (Dzik et al, 2006), both being elements of the non-classical type of response.…”
Section: Innate Immunity and Helminthsmentioning
confidence: 87%
“…In mice showing Th1 or Th2 response, two different types of macrophage activation have been described, M-1 (classical) involving induction of iNOS and nitric oxide production and M-2 (alternative) involving arginase induction (Mosser, 2003). We have shown that T. spiralis infection of guinea pigs does not induce nitric oxide production in lung macrophages (Dzik et al, 2002a;2002b) exposed to larval antigens when newborn larvae pass to the muscles. Instead, arginase activity is enhanced in these cells (Dzik et al, 2004), concomitantly with respiratory burst induction (Dzik et al, 2006), both being elements of the non-classical type of response.…”
Section: Innate Immunity and Helminthsmentioning
confidence: 87%
“…Polyclonal antibodies against TGF‐β, developed against a mixture of recombinant, human TGF‐β1, porcine TGF‐β1·2, porcine TGF‐β2 and recombinant, amphibian TGF‐β5; (0·375 mg in 0·5 mL of 0·9% NaCl) were injected twice, on the 3rd and 5th days after T. spiralis infection, into the vena femoralis of anaesthetized guinea pigs. In parallel, T. spiralis ‐infected animals, used as controls, were injected with 0·9% NaCl (21). Bronchoalveolar lavage was performed on the 6th day after infection.…”
Section: Methodsmentioning
confidence: 99%
“…Cyclosporin A-treatment resulted in an attenuation of immunological response in lungs of T. spiralis-infected guinea pigs, reflected by decreased lymphocyte infiltration into the pulmonary alveolar space (21). Under those conditions CsA significantly augmented extracellular arginase activity ( Figure 2).…”
Section: Influence Of Trichinella Spiralis Infection On Guinea Pig Almentioning
confidence: 97%
See 1 more Smart Citation
“…
Cyclosporin-A(CsA) is a very potent immunosuppressive agent which is widely used in transplantations and autoimmune diseases. Recent studies suggest an encouraging clinical effect for low-dose, long-term cyclosporin A treatment in different lung diseases [1,2,3,4,5]. Whether administration of CsA might be useful for lowering the dosage of steroids during the treatment of interstitial pneumonia, asthma and lung injuries [6,7,8] is presently a matter of controversy.
…”
mentioning
confidence: 99%